PENERAPAN PSAK 109 TENTANG AKUNTANSI ZAKAT, INFAK, DAN SEDEKAH DI LEMBAGA AMIL ZAKAT INSAN MADANI JAMBI - Khoyibah Ferenesia; Usdeldi Usdeldi; Muhamad Subhan (Nusantara Hasana Journal, 2026)
This Study Aims To Examine The Implementation Of Zakat, Infaq, And Sadaqah (ZIS) Accounting In The Financial Statement Presentation At Laz Insan Madani Jambi And To Analyze Its Compliance With The Statement Of Financial Accounting Standards (PSAK) No. 109. Employing A Qualitative Descriptive Approach, The Research Focuses On The Application Of PSAK 109 Concerning ZIS Accounting At The Insan Madani Amil Zakat Institution In Jambi. Data Collection Methods Include Interviews, Observations, And Documentation, While Data Analysis Is Conducted Descriptively. The Findings Indicate That The Implementation Of ZIS Accounting In The Financial Statements At LAZ Insan Madani Jambi Has Been Carried Out Systematically To Ensure Transparency And Accountability In Fund Management. Financial Reports Are Prepared By Segregating Fund Types And Recording Transactions Promptly, Thereby Supporting Accountability To The Public And Donors. This Demonstrates That LAZ Insan Madani Jambi Has Adhered To Financial Governance In Line With Accounting Standards And Islamic Sharia Principles. The Application Of ZIS Accounting At LAZ Insan Madani Jambi Aligns With The Provisions Of PSAK 109 Across Aspects Of Recognition, Measurement, Presentation, And Disclosure. Firstly, In Terms Of Recognition, LAZ Insan Madani Jambi Acknowledges And Records ZIS Receipts Immediately Upon Receipt, Whether In Cash Or Non-Cash Forms. Secondly, Regarding Measurement, Cash Funds Are Valued At Nominal Amounts, While Non-Cash Assets Are Measured At Fair Value. Thirdly, In Presentation, Financial Reports Are Prepared Separately For Each Fund Type (Zakat, Infaq/Sadaqah, And Amil Funds) And Included In The Statements Of Financial Position And Activities. Fourthly, In Disclosure, Adequate Information Is Provided, Encompassing Details Of Receipts, Distributions, Managed Assets, And Other Relevant Items, Reflecting LAZ Insan Madani Jambi's Efforts In Transparency And Accountability In Managing ZIS Funds.